Modified Anterolateral Approach in Minimally Invasive Total Hip Arthroplasty. Issue 3 (May 2015) - Tsai, Shang-Wen; Chen, Cheng-Fong; Wu, Po-Kuei; Chen, Tain-Hsiung; Liu, Chien-Lin; Chen, Wei-Ming
Purpose of the study: Minimally invasive procedures for total hip arthroplasty (THA) provide less surgery related trauma, and perhaps a fast recovery and satisfaction. Using modified instruments, we reported clinical follow-up data for a modified anterolateral approach. Basic procedures: Using specialised retractors to expose the acetabulum and femur, this single-incision technique preserved more gluteus medius tendon and provided access for soft tissue repair. The demographic data for 1003 patients undergoing THA with this technique are presented, including operative variables, complications, Harris Hip Score for clinical evaluation and cup inclination angle for radiographic evaluation. Average follow-up was 59 months (range 24-121). Main findings: In 1077 primary THAs performed in 1003 patients, the median wound length was 6 cm (range 4.8-9.2), median operation time was 68 minutes (range 45-112). The mean perioperative blood loss was 422 mls (range 56-990). The median cup inclination angle was 44 degrees (range 33-54), median acetabular version angle was 17° (range 12-24) median length of hospitalisation was 4 days (range 3-8). A total of 22 (2.0%) complications were noted including 5 cases of stem subsidence, 4 cup loosening, 5 greater trochanter fractures, 4 infections, 2 intraoperative proximal femur fractures and 2 iliopsoas impingement. In total, 13 (1.2%) received additional surgery. No neurovascular injury or dislocation was noted. For the clinical results, Harris Hip Score improved from 53 (range 33-67) preoperatively to 94 postoperatively (range 87-100). Principal conclusions: Minimally invasive surgery via this modified anterolateral approach is a safe and reliable method.